MANAJEMEN PELAYANAN BIMBINGAN MANASIK KBIH MUSLIMAT NU BALIKPAPAN DI MASA PANDEMI - Haliza Ati Ningsiwi (Institut Agama Islam Negeri Metro, 2022)
This study aims to analyze the management of manasik guidance services held during a pandemic at KBIH Muslimat NU Balikpapan and describe the responses of prospective pilgrims who take part in these manasik guidance activities. This research is a descriptive qualitative research, with a case study approach. The results showed that the management of the KBIH Muslimat NU Balikpapan Manasik guidance service during the Pandemic Period was carried out using four management functions namely planning, organizing, actuating and supervising. The congregation's response to the KBIH ritual service management stated that as much as 50% were very satisfied, 32% were satisfied, 12% were quite satisfied, and 6% were dissatisfied.